Muslimah Beauty: Negotiating Veiling, Piety and Commodity in the New Indonesian Public Sphere - Sunesti, Yuyun (DINIKA : Academic Journal of Islamic Studies, 2019)
This paper explores the veiling issues and the negotiation of piety among women in Komunitas Muslimah Beauty of Detik Forum. This paper examines to what extent this online community discusses hijab as fashion and piety? what the basis of the arguments for negotiating them? and how is piety constructed through commodity by women in that forum? The answers to this question are important to understand because they examine the assumption considering the lack of connection between piety and veiling when both are more materialized in such of commodity fetishism. To do this, I analyze the online discussion within the Komunitas Muslimah Beautiful in detik.com website. The findings of the paper inform both sociological understanding of the rise democracy in terms of the public sphere as well as the negotiation of women in their effort to connect veiling and piety within their online discussion.Â Keywords: agency, piety, commodity, public sphere, beauty